Variation and Use of Relativizers in the Spanish of Medellín, Colombia: A Corpus-Based Study - Franklin Yessid Arias Bedoya (Ikala: Revista de Lenguaje y Cultura, 2023)
The study of relativizers in the Spanish language has not been quite explored from a sociolinguistic point of view. A few research papers have analyzed varieties found in Santiago de Chile, Mexico City, Sevilla, and Madrid. Nevertheless, none of them has addressed a Colombian variety in depth. This variationist study aims to fill the gap by reporting the results of a correlational study focused on the use and variation of relativizers in the preseea-Medellín corpus. An anova test, a Games-Howell test, multiple Tukey’s tests, and pairwise comparisons t-tests with Bonferroni correction were run to identify the variables with significant effects (e.g., geographical position, gender, level of education, and social class). Results suggest that, while there is significant diatopic variation in the selection of relativizers, diastratic variables have a minor role in their frequency of use. It was also noted that while the use of the pronoun que tends to spread in all varieties of Spanish, the relative adjectives cuyo and cuanto continue their trend towards disuse. Further studies are necessary to determine if this tendency to simplification is related to psycholinguistic constraints (i.e. mental load) or functional aspects of Spanish. Finally, this study opens the doors to the analysis of relativizers in other varieties of Colombian Spanish from a sociolinguistic perspective.